Pendampingan penerapan Digitalisasi Usaha melalui Implementasi QRIS, dan Media Promosi pada UMKM Rakki Takoyaki dan Brand Nail Art Poisoned - Moch Rikal Farizy; Devano Febrilian Rozelly; Nizar Zulmi Ramadhan; Erika Sherren D; Ananda Velicia L.C; Muhammad Bintang Pratama; Moh. Dey Prayogo (Indo Publishing, 2026)
The development of digital technology in the modern era requires Micro, Small, and Medium Enterprises (MSMEs) to transform their business operations and marketing strategies. Digitalization is not limited to trading activities through online shops but also encompasses the modernization of financial payment systems and the optimization of digital promotional media to build a strong brand identity. The partners in this community service activity are Rakki Takoyaki, an MSME operating in the culinary sector, and Poisoned Nail Art, a brand operating in the beauty services sector. Both partners face similar operational challenges, namely transaction management that is still dominated by conventional cash methods and the suboptimal utilization of digital media to expand the promotional reach of their products and services. This mentoring activity aims to accelerate the business digitalization process for both partners through two main approaches: the implementation of the Quick Response Code Indonesian Standard (QRIS) cashless payment system and the utilization of social media as an interactive promotional tool. Through the implementation of QRIS, the payment transaction process at physical outlets becomes faster, safer, and automatically recorded, while simultaneously addressing the modern consumers' need for efficiency in cashless transactions